Fruit and seed morfometry, seed germination and seedling vigor of Parkia gigantocarpa - Demétrio Barros, Hellen Síglia [UNESP]; Cruz, Eniel David; Pereira, Adriano Gonçalves; da Silva, Edvaldo Aparecido Amaral [UNESP] (Universidade Federal do Paraná, 2020)
The objectives of this work were to characterize fruits and seeds and evaluate seed germination and seedling vigor from fifteen parent plants of Parkia gigantocarpa Ducke. The fresh weight, length, width, and thickness of fruits and seeds were determined. The germination was tested in a sand substrate, with four replications of 25 seeds per treatment (parent plants). The number of days for emergence, emergence percentage, emergence speed index, germination percentage, and seedling dry weight were evaluated. The fruits presented means for fresh weight, length, width, and thickness of 115.0 g; 621.3 mm; 60.8 mm, and 9.8 mm, respectively. The seeds presented means for fresh weight, length, width, and thickness of 1.1 g, 22.8 mm, 11.2 mm, and 7.0 mm, respectively. The emergence was fast and uniform, which occurred from the fifth to the sixth day after seeding, reaching 91% germination for the parent HB9, but not differing from the parents HB2, HB3, and HB6. The seedlings from the parents HB2, HB3, HB6, and HB9 were more vigorous due to their higher dry matter accumulation. The results found showed that, even belonging to the same species, P. gigantocarpa seeds from different parent plants present variability in biometric characteristics of fruits and seeds. The seed collected from different parent plants showed differences in germination capacity and seedling vigor.
Keywords: Fava-barriguda; Forest seeds; Parent trees; Seed biometry